Towards 3D Confocal Imaging with Laser-Machined Micro-Scanner - Oyman, Hilmi Artun; Efe, Baris Can; Icel, Mustafa Akin; Gokdel, Yigit Daghan; Ferhanoglu, Onur; Yalcinkaya, Arda Deniz (MDPI AG, 2018)
A micro-scanner made of stainless-steel is fabricated via laser cutting technology for 3D Lissajous confocal imaging. The multi-gimbaled structure of the device provides two orthogonal torsional modes and three different out-of-plane modes. Torsional modes can be used to achieve 2D scan and all of the out-of-plane modes can be used in changing the focus of the micro-scanner to achieve a 3D scanning pattern. One of the out-of-plane modes along with two orthogonal torsional modes can be employed for scanning a large depth-stack in sparse fashion while another out-of-plane mode can satisfy a much higher scan fill-rate with less field of view (FOV). Simulations of the micro-scanner are obtained using finite element method (FEM) software and compared with the characterization data gathered from Laser Doppler Vibrometer (LDV). Using various out-of-plane modes, the constructed fill patterns are simulated on MATLAB and fill rates compared.
Keywords: Lissajous scan; D imaging; laser-machined; confocal microscopy; stainless steel; magnetic actuation; micro-scanner; General Works